The energy-health-environment nexus: assessing the transboundary impacts of coal-fired power plants - Raja Dhar; Sayantan Sarkar; Chen Luo; Megha Anand; Shyamasree Dasgupta; Ujjwal Neogi; Apostolos Bossios; Rausan Zamir; Mohammad Shoeb; Joyanto Routh (Frontiers in Public Health)
Point source emissions from large coal-fired power plants are pivotal in the energy-health-environment nexus, impacting energy security, air quality, and public health outcomes. Despite this, there is a lack of interdisciplinary prospective studies focusing on the effects of power plant emissions on the population residing downwind. To address this gap, a comprehensive, multicenter, interdisciplinary study on a transboundary scale (India and Bangladesh) has been launched, which includes modeling power plant emissions, seasonal collection of particulate matter and its chemical analysis, socioeconomic surveys of the case (downwind) and control (upwind) populations, lung health assessments, and transcriptomic analyses of blood samples. The outcomes will provide quantitative estimates of power plant impacts on air quality, lung health, and blood markers associated with pulmonary complications. This approach comprehensively assesses the population health impacts of power plant emissions. Moreover, by conducting lung tests in patients on-site, the health team captures an actual snapshot of air pollution. The study establishes causality between power plant emissions, particulate matter characteristics, and population exposure levels while accounting for social, demographic, and economic factors, the study establishes. By integrating diverse techniques, quantitative and qualitative methods, and perspectives, this study aims to enhance scientific understanding of the health and environmental risks and the socioeconomic burden associated with coal-based energy generation in developing countries.